(3ehba TQGM GdMOjK GdfHhj ef eSGFd GdYbjOI ef GdbQf GdQGHY Edi GdbQf GdKGef GdgLQjjf (B/ s - (3MGaX YGThQ MGaXs; (3CMeO bhTJj (B: s; (3YHOGdMejO YHOGdefYe eOchQ (B: s ((3GdbGgQI (B: s (3MGaX YGThQ MGaX (B: s, 2013)
(3jhVM GdHMK ehba TQGM GdMOjK ef eSGFd GdYbjOI(B: (3h gh jVe CQHYI CHhGH(B: (3GdHGH GdChd(B: (3h gh HGH JegjOi jJcde Ydi TQhM GdMOjK GdfHhi h eSGFd GdYbjOI ajgG(B: (3h HYV GdeSGFd GdJegjOjI cGdehba ef Yde GdcdGe(B: (3Ke GdHGH GdKGfi h jJYdb HeSGFd GdEdgjGJ(B: (3h GdHGH GdKGdK(B: (3jJYdb HeSGFd GdfHhGJ(B: (3h GdHGH GdQGHY(B: (3jJYdb HeSGFd GdSeYjGJ(B: (3h ajg GdcdGe Ydi GdedGFcI h GdcJH h Gdjhe GdCNQ(B. (3h jQcR GdHMK Ydi LhGfH GdYbjOI GdUMjMI GdJi LGAJ HgG GdSfI GdfHhjI GdeWgQI(B: (3h ajg ebGQfI Hjf TQGM GdMOjK h YdeGA GdcdGe(B: (3h HjGf dePgH Cgd GdSfI h QOhO Ydi ePGgH Cgd GdHOY h GdCghGA s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdadSaI GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3YbjOIs; (3Yde GdcdGes; (3adSaI ESdGejIs